2002
DOI: 10.1098/rspb.2002.1966
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding and experience affect response to climate change by endangered woodpeckers

Abstract: In recent decades, female red-cockaded woodpeckers (Picoides borealis) have laid eggs increasingly earlier in response to a changing climate, as has been observed in several other bird species breeding at north temperate latitudes. Within each year, females that lay earlier are more productive than females that lay later. However, inexperienced females, experienced females who change mates and inbred birds have not adjusted to the changing climate by laying earlier, and have suffered reproductive costs as a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 48 publications
(57 reference statements)
3
45
1
Order By: Relevance
“…Coltman et al 1998Coltman et al , 1999Coulson et al 1998aCoulson et al , 1999Marshall and Spalton 2000;Slate et al 2000a;Amos et al 2001;Hö glund et al 2002;Schiegg et al 2002;Slate and Pemberton 2002;Acevedo-Whitehouse et al 2003;Reid et al 2003). Our data lend further support to this trend, revealing a pattern in which males born to less-related parents tend to father more pups.…”
Section: Discussionsupporting
confidence: 73%
“…Coltman et al 1998Coltman et al , 1999Coulson et al 1998aCoulson et al , 1999Marshall and Spalton 2000;Slate et al 2000a;Amos et al 2001;Hö glund et al 2002;Schiegg et al 2002;Slate and Pemberton 2002;Acevedo-Whitehouse et al 2003;Reid et al 2003). Our data lend further support to this trend, revealing a pattern in which males born to less-related parents tend to father more pups.…”
Section: Discussionsupporting
confidence: 73%
“…Overall, the laying date of RCWs advanced over the study period, supporting previous results from our study population (Schiegg et al 2002, Garcia 2014). The RCW is one of many species in which an advanced laying date in response to increasing temperatures has been documented (e.g., Crick and Sparks 1999, Dunn and Winkler 1999).…”
Section: Discussionsupporting
confidence: 78%
“…The advancement in laying date was greater for birds on Safe Harbor properties compared with those on control properties. Previous research on this population has indicated that young females, inexperienced females, and experienced females breeding with a new mate advance their laying dates less than other birds in response to climate change (Schiegg et al 2002). Thus, higher turnover of female breeders on control properties is a potential mechanism that could have produced the difference that we observed.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations